Religious transnational actors and soft power - Haynes, Jeffrey (Religion and international security, 2012)
This study looks at the dynamics of this new religious pluralism as it influences the global political landscape. Several specific transnational religious actors are examined in the chapters including: American Evangelical Protestants, Roman Catholics, the Organisation of the Islamic Conference, Sunni extremist groups (al Qaeda and Lashkar-e-Taiba), and Shia transnational networks. While varying widely in what they seek to achieve, they also share an important characteristic: each seeks to use religious soft power to advance their interests.